Тенденції розвитку вищої освіти та необхідність викладацького лідерства сучасних педагогів - Резнік, Світлана Миколаївна (Черкаський національний університет ім. Богдана Хмельницького, 2020)
У статті узагальнено тенденції розвитку вищої освіти відповідно до соціокультурних трансформацій сучасного суспільства та на цій основі визначено особливу актуальність та практичну потребу розвитку викладацького лідерства у студентів та викладачів в системі сучасної педагогічної освіти України.

One of the most urgent issues in the pedagogic theory and practice is their correlation with the challenges to modern society. The rapid development of technology and dramatic changes in the socio-cultural sphere call for the search for new ways to improve the present-day higher education. The purpose of the article is to generalize the tendencies in the development of higher education and to substantiate on this basis the need in teachers’ leadership in present-day teachers. Result. The tendencies in higher education development have been analyzed and generalized in according with the following socio-cultural determinants: globalization, computerizing, the VUCA-environment, the «clip-thinking» effects, the cognizant society, segregation, ecology problems, the development of the civil society, the demographic ageing of the population, the leisure civilization, etc. Considering the mentioned tendencies, it has been determined that purposeful development of teachers’ leadership in pedagogues should be among the important ways to raise the quality of present-day education. A teacher-leader is a conduit for changes in his/her higher education institution and accepts the responsibility for the wide-scaled introduction of pedagogic innovations, development of new programs, and other sectors of work, thus making an impact on the activity of the whole education institution as such. In Ukraine, hardly any attention is paid to the development of teachers’ leadership in neither higher education institutions’ programs, nor in qualification improvement programs, or in the formal or informal education systems. The authors think it necessary to introduce changes to the content of the pedagogic education in Ukraine and to purposefully develop teachers’ leadership in students and teachers. Conclusion. There have been generalized the tendencies in the development of higher education in accordance with the socio-cultural transformations of the present-day society, and on this basis there were determined the urgency and practical need in teachers’ leadership development in students and teachers within the present-day system of higher education of Ukraine.
Tendencies in higher education development and the need in teachers’ leadership in present-day teachers
Keywords: викладацьке лідерство; соціокультурні детермінанти розвитку освіти; тенденції розвитку вищої освіти; teachers’ leadership; socio-cultural determinants of education’s development; tendencies in development of higher education